Coping guidelines for women who have experienced the psychological impact of Intimate Partner Violence (IPV) in Ehlanzeni District - Nyathi, Charmain Sandra (My University, 2022)
The study investigated the phenomena of Intimate Partner Violence (IPV) in women in Ehlanzeni District, Mpumulanga, South Africa in order to develop coping guidelines. This is because, one in every four, or a quarter (25%) of all women in South Africa, are assaulted by their partners every week. The study adopted a qualitative approach utilising an exploratory, hermeneutic phenomenological research design. A non-probability sample of ten women, who were victims of IPV, was used. The theoretical framework for the study was Afrocentric theory. This framework was used so that the investigation was underpinned by truly African concepts. The study was conducted at Victim Empowerment Programmes in Mkhuhlu and Acornhoek, Ehlanzeni District in Mpumalanga Province. Semi-structured interviews were used as data collection instruments and analaysed using thematic analysis (TA). The following themes and sub-themes emerged out of the data: Theme 1: Understandings of Intimate Partner Violence (IPV); Theme 2: Intimate Partner Violence (IPV) experienced by participants; Theme 3: Reasons for Intimate Partner Violence (IPV); Sub-theme 3.1: Alcohol as a facilitator of IPV; Sub-theme 3.2: Early parenthood as a facilitator of IPV; Sub-theme 3.3: Poverty as a facilitator of IPV and Sub-theme 3.4: Observed behaviour as a facilitator for IPV; Theme 4: The role of lobola/culture in Intimate Partner Violence (IPV); Theme 5: What makes participants stay in abusive relationships (marriages) and Theme 6: Steps, or interventions, taken by participants in order to cope with Intimate Partner Violence (IPV). Based on these findings it was recommended that a study of male perceptions towards IPV, and a nationwide study or studies on IPV, be carried out under the auspices of the Department of Social Development (DoS) and/or the Department of Health (DoH) with the help of relevant non-governmental organisations (NGOs). Coping guidelines for women victims of IPV were developed out of the research findings.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2022
Keywords: Coping guidelines; Psychological impact; Inmate partner violence; Dating violence; Intimate partner violence; Abused women -- South Africa -- Mpumalanga; Women -- Abuse of -- South Africa -- Mpumalanga; Family violence -- South Africa -- Mpumalanga